Development of indoor positioning system by using phone equipped sensors - An, Qi (2016)
Indoor Positioning System (IPS) has gain its popularity recently. This is driven by the ineffectiveness of Global Positioning System signals in indoor environment, as well as the more and more complex building structure. IPS captures data of coordinate variables from various wireless signals, e.g. Wi-Fi signals, Bluetooth signals, etc. Nevertheless, data from such signals are normally inaccurate due to unstable factors, including the influence from human movement within indoor environment, ambiguity of single sensor signal quality, etc. This project aims to recover logical coordinate data which are able to correctly reflect the actual position of the sensors. It is accomplished by performing structured analysis on input data of raw coordinate information. Coordinate and speed information of previous timings, as well as normal human walking speed are applied in order to find better and more accurate results. The objective of this project has generally been fulfilled. Performance of indoor navigation is improved with the help of data analysis process.